Skyscrapers architectural form effects on airflow - Soo, Cindel Yung Yung; Lokman Hakim Ismail; Izudinshah Abd Wahab; Nur Amalina Hanapi (Penerbit Universiti Kebangsaan Malaysia, 2021)
In today’s architectural world, skyscrapers building has been a common typology of building in urban areas despite challenges on its construction, economy feasibility, comfort of occupants and even on its technical aspects like aerodynamic characteristics towards wind. In relation to the air pressure effect on building surfaces due to the mass buildings development, this paper reviews on the varying building forms effects to the wind ventilation circulating the surrounding area. For such building, aerodynamic forces include three modes of action: along wind, across wind and torsional modes. To overcome such challenges, ‘Aerodynamic Mitigation’ techniques and ‘Aerodynamic Shape Optimization’ techniques were used. Basic shapes and modified shapes of square prism, cylindrical and pyramidal were tested through wind tunnel using Airflow meter with Pitot tube to determine the aerodynamic characteristics in winds from different directions. The study also shows the significance of aerodynamic modifications as an effective design approach in terms of mitigating wind excitation. The results of these experiments have led to comprehensive understanding of the aerodynamic characteristics of skyscrapers with various configurations. It is proven to an extent that aerodynamic modifications in building shape could moderate wind responses when compared to original building shape. By comparison, cylindrical shows the best aerodynamic performance followed by pyramidal and square prism.